Mass formula for self-dual codes over Fq+uFq+u² Fq - Espina,Trilbe Lizann F. (Institute of Mathematics, College of Science, University of the Philippines Diliman, 2013)
We consider codes over the finite ring Rq = Fq +uFq +u² Fq, where Fq is the finite field of order q and + u³ = 0. We establish amass formula for self-dual codes over rq and classify such codes of length n < 4 for q < 10.